Case report from Mayo clinic - Pinn, Melva E. (Radiology and oncology (Ljubljana), 2007)
Tumors of the Bartholin gland are rare, comprising less than 5% of all vulvar malignancies. Treatment is largely based on that of vulvar and anal squamous cell carcinomas. A case of invasive, grade 4, poorly differentinted squamous cell carcinoma of the Bartliolin gland is presented. Our pntient, a 47-year-old woman, had a Ivistory significant for cervical intraepithelial neoplasia treated with Ionization, type 2 diabetes mellitus, and tobacco use. The course of treatment included preoperative radiotherapy plus 5 fluorouraciland cisplatin chemotherapy, followed by restaging and posterior exenterc`tion in combination with vaginal reconstruction.
Keywords: Bartholinijeve žleze; Bartholin's Glands; Drug Therapy; Methods; Middle Age; novotvorbe; Radioterapija; Radiotherapy; Srednja leta; Surgery; therapy; tumor; vagina; Vagina, novotvorbe; Vaginal Neoplasms; zdravljenje